Generación de condensado con celdas de Peltier - Moreno-Parra, Yeison Dubiel; Pérez-Valdeblanquez, Henry Erik; Garzón-González, Enrique Yamid (Visión electrónica, 2018)
This article details the process of the construction of a device that uses peltier cells as a way to obtain water from the environment through condensation. To achieve this, we chose to use the Freescale FRDM-KL25Z development board, which allows regulating the voltage reaching the cell through PWM modulation. In addition, the microcontroller is responsible for reading environmental variables such as relative humidity, ambient temperature and temperature on the cold side of a Peltier cell. In order to be able to vary the PWM keeping the temperature of the cold side of the cell below the point of spray obtaining a condensate and a possible water drip.